cho biết \(\cos\alpha\)+\(\sin\)\(\alpha\)=m.Tính P=\(\left|\cos\alpha-\sin\alpha\right|\)theo m
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\dfrac{\left(sina+cosa\right)^2-\left(sina-cosa\right)^2}{sina.cosa}=4\\ VT=\dfrac{sin^2a+2sinacosa+cos^2a-sin^2a+2sinacosa-cos^2a}{sinacosa}\\ =\dfrac{4sinacosa}{sinacosa}=4=VP\)
a: \(S=cos^2a\left(1+tan^2a\right)=cos^2a\cdot\dfrac{1}{cos^2a}=1\)
b: \(VP=\dfrac{1+sin2a-1+sin2a}{\dfrac{1}{2}\cdot sin2a}=\dfrac{2\cdot sin2a}{\dfrac{1}{2}\cdot sin2a}=4=VT\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(B=\left(sina+cosa\right)^2-\left(cosa-sina\right)^2=\left(sin^2a+2sinacosa+cos^2a\right)-\left(cos^2a-2cosasina+sin^2a\right)=sin^2a+2sinacosa+cos^2a-cos^2a+2cosasina-sin^2a=4sinacosa\)\(A=\dfrac{1+2sinacosa}{sina+cosa}=\dfrac{sin^2a+cos^2a+2cosasina}{sina+cosa}=\dfrac{\left(sina+cosa\right)^2}{sina+cosa}=sina+cosa\)
C mik bó tay
![](https://rs.olm.vn/images/avt/0.png?1311)
Lời giải:
\(A=(\sin ^2a)^3+(\cos ^2a)^3+3\sin ^2a\cos ^2a(\sin ^2a+\cos ^2a)\)
\(=(\sin ^2a+\cos ^2a)^3=1^3=1\)
\(B=(\cos ^2a+\sin ^2a-2\sin a\cos a)+(\cos ^2a+\sin ^2a+2\sin a\cos a)\)
\(=(1-2\sin a\cos a)+(1+2\sin a\cos a)=2\)
\(C=\frac{(\cos ^2a+\sin ^2a-2\sin a\cos a)-(\cos ^2a+\sin ^2a+2\sin a\cos a)}{\sin a\cos a}=\frac{(1-2\sin a\cos a)-(1+2\sin a\cos a)}{\sin a\cos a}\)
$=\frac{-4\sin a\cos a}{\sin a\cos a}=-4$
![](https://rs.olm.vn/images/avt/0.png?1311)
Đề sai em
Đề đúng: \(\dfrac{\left(sina+cosa\right)^2-\left(sina-cosa\right)^2}{sina.cosa}=4\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Lời giải:
\(M=\frac{(\cos a-\sin a)^2-(\cos a+\sin a)^2}{\cos a\sin a}\)
\(=\frac{\cos ^2a-2\sin a\cos a+\sin ^2a-(\cos ^2a+2\sin a\cos a+\sin ^2a)}{\cos a\sin a}\)
\(=\frac{-4\sin a\cos a}{\cos a\sin a}=-4\)
\(cosa+sina=m\)
=>\(\left(cosa+sina\right)^2=m^2\)
=>\(1+2\cdot sina\cdot cosa=m^2\)
=>\(2\cdot sina\cdot cosa=m^2-1\)
\(P=\left|cosa-sina\right|\)
\(=\sqrt{\left(cosa-sina\right)^2}\)
\(=\sqrt{cos^2a+sin^2a-2cosa\cdot sina}\)
\(=\sqrt{1-\left(m^2-1\right)}=\sqrt{2-m^2}\)